Editors' Introduction - Jackie Smith; Isaac Kamola; Alexandre White; Patrick Manning (Journal of World-Systems Research, 2020)
Editors' Introduction to Journal of World-Systems Research Volume 26, Issue 1 (Winter/Spring 2020)